Difficult situations and ways of managing them in paediatric nurses’ practise - Perek, Mieczysława; Kózka, Maria; Twarduś, Krystyna (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Introduction. Paediatric nurses are continuously subject to difficult situations because they are responsible for the most important values such as health and life of a child. Aim. The aim of the study was to recognise difficult situations in paediatric nurses’ practise, and ways of solving problems in nursing care. Material and methods. Study group comprised of 108 nurses employed in paediatric departments in Malopolska Province. The study used home-made survey questionnaire, CISS questionnaire for examination of reactions on difficult situations and KWEP questionnaire for measurement of emotional support received because of problems originating from professional work. Results and conclusions. Results show that there are many difficult situations in paediatric nurses’ practise. Those situations result from the nature of the work, its organization and interpersonal relationships.